Cloud computing : business trends and technologies - Faynberg, Igor.; Lu, Hui-Lan.; Skuler, Dor. (Chichester, West Sussex, UK : John Wiley & Sons, Ltd., 2016)
Cloud Computing: Business Trends and Technologies provides a broad introduction to Cloud computing technologies and their applications to IT and telecommunications businesses (i.e., the network function virtualization, NFV). To this end, the book is expected to serve as a textbook in a graduate course on Cloud computing. The book examines the business cases and then concentrates on the technologies necessary for supporting them. In the process, the book addresses the principles of – as well as the known problems with – the underlying technologies, such as virtualization, data communications, network and operations management, security and identity management. It introduces, through open-source case studies (based on OpenStack), an extensive illustration of lifecycle management. The book also looks at the existing and emerging standards, demonstrating their respective relation to each topic. Overall, this is an authoritative textbook on this emerging and still-developing discipline, which •Guides the reader through basic concepts, to current practices, to state-of-the-art applications. •Considers technical standards bodies involved in Cloud computing standardization. •Is written by innovation experts in operating systems and data communications, each with over 20 years’ experience in business, research, and teaching.
6.1 Data Center Basics6.1.1 Compute; 6.1.2 Storage; 6.1.3 Networking; 6.2 Storage-Related Matters; 6.2.1 Direct-Attached Storage; 6.2.2 Network-Attached Storage; 6.2.3 Storage Area Network; 6.2.4 Convergence of SAN and Ethernet; 6.2.5 Object Storage; 6.2.6 Storage Virtualization; 6.2.7 Solid-State Storage; References; 7 Operations, Management, and Orchestration in the Cloud; 7.1 Orchestration in the Enterprise; 7.1.1 The Service-Oriented Architecture; 7.1.2 Workflows; 7.2 Network and Operations Management; 7.2.1 The OSI Network Management Framework and Model; 7.2.2 Policy-Based Management.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Cloud computing; Infonuagique; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Cloud computing